Trends and cost structure of drug-based secondary prevention of ischemic strokes - Konstantin Kohlhase; Ferdinand O. Bohmann; Christian Grefkes; Adam Strzelczyk; Laurent M. Willems (Neurological Research and Practice)
Abstract Background Advances in secondary stroke prevention, including direct oral anticoagulants (DOACs), dual antiplatelet therapies (DAPT), and cardiovascular risk management, have changed costs over the past decade. This study aimed to evaluate annual treatment costs and trends in drug-based secondary prophylaxis after ischemic strokes. Methods Annual treatment costs were evaluated using the net costs per defined daily dosage (DDD) of discharge medications for ischemic stroke patients treated in 2020 at the University Hospital Frankfurt, Germany. Evaluated drugs included acetylsalicylic acid, adenosine diphosphate inhibitors, DOACs, vitamin K antagonists, lipid-lowering drugs (LLD), antihypertensives (AHT), and oral antidiabetics (OD). Kruskal–Wallis test examined intergroup differences in substance groups and stroke etiologies. DDD development between 2004 and 2021 was further evaluated for significant trend changes using an interrupted time series analysis. Results The study included 422 patients (70.5 ± 12.9 years, 43.1% female). Etiologies divided into large-artery atherosclerosis (29.9%), cardioembolic (25.6%), cryptogenic (26.8%), and small-vessel disease (17.8%). The total estimated annual drug expenditure was € 241,808; of which 51.6% was due to DOACs (median € 1157 [Q1–Q3:1157–1157], p < 0.006), 20.0% to AHTs (€127.8 [76.7–189.8]), 15.7% to ODs (€525.6 [76.7–641.5]), and 8.7% to LLDs (€43.8 [43.8–43.8]). Cardioembolic strokes had the highest annual costs per patient (€1328.6 [1169.0–1403.4]) with higher expenditure for DOACs (p < 0.001) and AHTs (p < 0.026). DAPT costs were highest for large-vessel strokes (p < 0.001) and accounted for 2.5% of total costs. There was a significant trend change in DDDs for clopidogrel in 2010 (p < 0.001), for prasugrel in 2017 (p < 0.001), for ASA in 2015 (p < 0.001) and for DOACs in 2012 (p = 0.017). Conclusions DOACs for cardioembolic strokes were the primary cost driver in drug-based secondary stroke prevention, whereas permanent ASA and DAPT only accounted for a minor cost proportion. LLDs were associated with lower costs than AHTs and ODs. There were significant changes in DDDs for the respective substances, whereas the costs for DOACs as the most expensive pharmaceuticals remained widely stable across the last decade.